1985
DOI: 10.1084/jem.161.5.1213
|View full text |Cite
|
Sign up to set email alerts
|

ras Oncogene p21 expression is increased in premalignant lesions and high grade bladder carcinoma.

Abstract: ras Oncogene p21 antigen is present in the most superficial cells of the normal bladder urothelium, as demonstrated by immunohistochemical staining. The pattern and intensity of p21 staining of cells in epithelial hyperplasia and low grade bladder carcinoma were similar to that seen in the normal urothelium. In contrast, epithelial cells in "premalignant" (dysplastic) lesions and high grade carcinomas exhibited an intense staining reaction for p21 antigen. ras p21 may be a useful marker for the malignant poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1
4

Year Published

1987
1987
1995
1995

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(65 citation statements)
references
References 17 publications
2
58
1
4
Order By: Relevance
“…The maintenance of the noninvasive phenotype of the control pSV2neo-transfected pooled parental line RT-4 and of the RT-4-cr-3 and RT-4-mr-7 plus the acquisition of an invasive phenotype by RT-4-cr-1 and RT4-mr-10 was clear and striking. This modulation of the invasive phenotype by manipulation of the level of HRAS appears to be consistent with clinical data showing correlations of enhanced invasion with greater degrees of p21 expression (8). In addition, it is consistent with a model postulating possible mutations in the promoter (13) or in the coding regions (14) of the HRAS gene as "second hits," inducing tumor cell invasion.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The maintenance of the noninvasive phenotype of the control pSV2neo-transfected pooled parental line RT-4 and of the RT-4-cr-3 and RT-4-mr-7 plus the acquisition of an invasive phenotype by RT-4-cr-1 and RT4-mr-10 was clear and striking. This modulation of the invasive phenotype by manipulation of the level of HRAS appears to be consistent with clinical data showing correlations of enhanced invasion with greater degrees of p21 expression (8). In addition, it is consistent with a model postulating possible mutations in the promoter (13) or in the coding regions (14) of the HRAS gene as "second hits," inducing tumor cell invasion.…”
Section: Discussionsupporting
confidence: 71%
“…These studies have, in the main, concentrated on estimating the level of the RAS gene protein product, p21, in tumors of various stages (8). The results have shown that in general, there is a correlation between levels of p21 and the degree of tumor invasiveness similar to what has been observed in some other types of tumor (9)(10)(11).…”
Section: Introductionmentioning
confidence: 63%
“…The usual techniques for studying oncogene structure and/or function include blotting studies of DNA or of its RNA message and investigation of the biochemical function of protein products. Immunoblotting studies indicate that ras genes are probably involved in (normal) growth control (Shih & Weeks, 1984;McGrath et al, 1984;Sweet et al, 1984;Bar-Sagi, 1989) and that their alteration plays a role in causing several types of human haematological and solid tumours (Viola et al, 1985;Thoret et al, 1984;Lundy et al, 1986;Thein et al, 1986;Liu et al, 1987;Bos et al, 1987;Senn et al, 1988;Pedersen-Bjegard et al, 1988;Hirai et al, 1988).…”
Section: Resultsmentioning
confidence: 99%
“…Newer potential prognostic factors may be utilized to select patients who are potentially suitable for organ conservation (60)(61)(62)(63)(64)(65)(66)(67)(68). There has been a proliferation of studies concerning markers of drug resistance, D N A content, expression of epidermal growth factor receptor, chromosome abnormalities, and oncogene expression, and angiogenesis.…”
Section: Prognostic Factors For Bladder Preservationmentioning
confidence: 99%